Letter - Brook, Charles Wortham, 1901-1983
041-0085-001 61-2, Lincoln's Inn Fields, W.C.2. 18th December 1936. Sir Walter Citrine, K.B.E. Joint Secretary, National Council of Labour, Transport House. Smith Sq. S.W.1. Dear Sir Walter, Owing to very great pressure of work which I am afraid I have had to sorely neglect during the past few months, I have had to relinquish the Honorary Secretaryship of the Spanish Medical Aid Committee. I am very satisfied at the progress which has been made, and I should like to take the opportunity of thanking you most sincerely for the many kindnesses that I have received from you and from your colleagues. May I also express my very great appreciation of the fine co-operation which I have received from Dr. Morgan. Yours sincerely, Charles Brook 292/946/41/85